(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess the frequency of expulsion of postpartum intrauterine contraceptive device (PPIUCD) inserted in females presenting after delivery at term. Study Design: Descriptive case series. Place & Duration of Study: Department of Obstetrics &Gynaecology, Services Hospital, Lahore for a period of six months. Methodology: A total 210 cases were included through Non-Probability, PurposiveSampling.Informed consent anddemographic information were obtained. Females who underwent normal vaginal delivery were inserted IUD. They were followed for 6 weeks and x-ray was performed to confirm expulsion. All the data was collected using the proforma. SPSS Windows software (version 16.0) was used for data analysis. Quantitative data like age was presented as mean and standard deviation. Qualitative data like parity, IUD expulsion were presented as frequency and percentage. Results: The mean age of females in this study was 29.95±5.64 years. There were 114 (54%) females who had age range 20-30 years and 96 (46%) female fell in age range 31-40 years. The expulsion was observed in 17 (8.1%) cases while in remaining 193 (91.9%) cases, IUD was in proper place.Among the females of age 20-30 years, the expulsion was observed in 9 (7.9%) cases while 105 (92.1%) cases had IUD in proper place. Among the females of age 31-40 years, the expulsion was observed in 8 (8.3%) cases while 88 (91.7%) cases had IUD in proper place. There was insignificant difference observed between both age groups for expulsion of IUD (P>0.05). Conclusion: Thus it was concluded through results of this study that expulsion of PPIUCD is low, and controversy in results of previous literature has been solved.